The influencing factors of entrepreneurial intention: A comparative study between public (UUM) and private (KUIN) universities in northern Malaysia - Adetola, Adelaja Ayotunde (2015)
Entrepreneurial Intention seems to have been an exhausted area in management. However, this study, using Shapero’s model of entrepreneurial intention investigates factors that influence students’ entrepreneurial intention in a new dimension by conducting a comparative study between public and private universities sampling students there in. Addition to this, the study examines the influence of religion (in terms of religious supports) if treated as an independent variable rather than it being treated under demographic variable as most study did. Findings concludes that, there is no significance difference between entrepreneurial intention between public and private universities in general, although, factors contributing to their entrepreneurial intentions differs individually, this conclusion is based on the variables investigated, that is, entrepreneurial education, social supports and religious supports Entrepreneurial education is found to be the most significant factors at both institutions, religious support is found not to be a relevant factor among the two universities surveyed. Social support is statistically significant among public (UUM) students’ samples but it is not statistically significant among samples drawn from private (KUIN) university.